Antibiotics and malachite green residues in farmed rainbow trout (Oncorhynchus mykiss) from the Iranian markets: A risk assessment. Issue 2 (1st February 2017) - Adel, Milad; Dadar, Maryam; Oliveri Conti, Gea
ABSTRACT: Antibiotic and malachite green residues in farmed rainbow trout muscles were determined by high-performance liquid chromatography for a food risk assessment. The surveillance was carried out on total of 120 rainbow trout fillets, all fishes were randomly sampled from 20 fish markets of Iran. All antibiotics were detected in the range of 0.42–1.20 μg/g for Oxytetracycline, 0.02–0.34 μg/g for Enrofloxacin, 0.21–2.61 μg/g for Florfenicol, and finally 0.02–0.89 μg/g for Malachite green. Our results showed that 99 (82.5%), 36 (30%), 56 (46.6%), and 70 (58.4%) samples contained detectable residues of Oxytetracycline, Enrofloxacin, and Florfenicol antibiotics, and Malachite green, respectively. Our results showed that fish farmers use these drugs in large scale. Further investigations are needed to prevent: the foodborne risk to consumers, the possible environmental contamination, and the antimicrobial resistances.